2022
DOI: 10.3389/fmicb.2022.1089092
|View full text |Cite
|
Sign up to set email alerts
|

Acanthamoeba spp. aggregate and encyst on contact lens material increasing resistance to disinfection

Abstract: IntroductionAcanthamoeba keratitis is often caused when Acanthamoeba contaminate contact lenses and infect the cornea. Acanthamoeba is pervasive in the environment as a motile, foraging trophozoite or biocide-resistant and persistent cyst. As contact lens contamination is a potential first step in infection, we studied Acanthamoeba’s behavior and interactions on different contact lens materials. We hypothesized that contact lenses may induce aggregation, which is a precursor to encystment, and that aggregated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We tested rAbs versus the model Neff strain of Ac, as well as Acanthamoeba species/strains from the ATCC collected by Monica Crary, who studies their binding to contact lenses (24,27). Segments of 18S RNA genes were amplified from trophozoites, cloned, and sequenced to confirm the genotype of 11 Acanthamoeba species/strains prior to encystation and testing with rAbs (13)(14)(15)(16).…”
Section: Rabbit Antibodies Tomentioning
confidence: 99%
See 1 more Smart Citation
“…We tested rAbs versus the model Neff strain of Ac, as well as Acanthamoeba species/strains from the ATCC collected by Monica Crary, who studies their binding to contact lenses (24,27). Segments of 18S RNA genes were amplified from trophozoites, cloned, and sequenced to confirm the genotype of 11 Acanthamoeba species/strains prior to encystation and testing with rAbs (13)(14)(15)(16).…”
Section: Rabbit Antibodies Tomentioning
confidence: 99%
“…Cyst walls, which form when trophozoites are starved of nutrients, protect free-living Acanthamoebae from osmotic shock in freshwater or drying in the air [21,22]. The cyst wall also makes Acanthamoebae resistant to disinfectants used to clean surfaces, alcohol-based hand sanitizers, sterilizing agents in contact lens solutions, and/or antibiotics applied to the eye [23][24][25][26][27]. While trophozoites cause damage to corneal epithelial cells, AK is most often diagnosed by microscopic identification of cysts in corneal scrapings [1,2,28].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this issue, second generation silicon hydrogel lenses have been developed and trophozoite attachment rates for this generation of lenses were much lower than for the first generation and not statistically different from those of conventional hydrogel lenses ( Beattie et al, 2006 ). Recently, Campolo et al (2022) found that some contact lens materials are more conducive to cyst formation than the natural environment with encystation occurring within as little as 4 h of incubation. They hypothesized that aggregation of cysts directly obstructs multi-purpose solutions from disinfecting Acanthamoeba , which further indicates that contact lens materials may need to be reevaluated in the future as infection incidence increases ( Campolo et al, 2022 ).…”
Section: Acanthamoeba Related Diseasesmentioning
confidence: 99%
“…Recently, Campolo et al (2022) found that some contact lens materials are more conducive to cyst formation than the natural environment with encystation occurring within as little as 4 h of incubation. They hypothesized that aggregation of cysts directly obstructs multi-purpose solutions from disinfecting Acanthamoeba , which further indicates that contact lens materials may need to be reevaluated in the future as infection incidence increases ( Campolo et al, 2022 ). The adhesion of trophozoites and cysts to the surface of CLs depends on the structure of both.…”
Section: Acanthamoeba Related Diseasesmentioning
confidence: 99%
“…Overall, there is a lack of research and understanding regarding Acanthamoeba motility and how it relates to contact lens use, or how it is impacted by CLC disinfection. We recently published a novel method regarding Acanthamoeba motility on control surfaces with and without available nutrients [ 8 ], and found that amoebae were able to remain motile for at least 12 h even in the absence of nutrients [ 9 ]. This indicated that amoebae could potentially travel substantial distances on contaminated lenses, or from a lens to a cornea and into the corneal epithelium, within the normal period of time for either wearing a lens or in which the lens is in its case.…”
Section: Introductionmentioning
confidence: 99%